(Ustavno)sodna farsa o rovokopaču - Možina, Damjan (Podjetje in delo, 2017)
The article presents a damages case about which Slovenian courts have been deciding for 20 years. The claimant was at the construction site in his capacity as the head of maintenance of aqueduct, whose duty was to prevent cutting into existing aqueducts. He suddenly climbed onto a construction machine - a trencher - in operation and started moving the drive lever. As a consequence, the trencher moved and tipped over, heavily injuring the claimant. The lower courts have upheld the claim to the amount of 50% due to the contribution of the claimant to the accident. The Supreme Court decided that the accident occurred entirely due to an unreasonable behaviour of the claimant, relieving the respondents of liability. The Constitutional Court set the judgement aside due to insufficient reasoning. In the second attempt, the Supreme Court offered a more detailed reasoning but the Constitutional Court again set aside the judgement. The Supreme Court tried again and the Constitutional Court set aside the judgement for the third time, this time relying on "blatant incorrectness" (arbitrariness) of the judgement. Furthermore, the Constitutional Court decided on the merits of the case (in part).. In the article, the decisions of the Constitutional Court are subjected to a critical analysis. In the opinion of the author, the Constitutional Court did not have jurisdiction to hear the case. Furthermore, in terms of substantive law (tort law) it adopted a wrong decision.
Keywords: constitutional civil law; contribution of the claimant; fault liability; jurisdiction of the Constitutional Court; krivdna odgovornost; nepogodbeno odškodninsko pravo; non-contractual law of damages; objective liability; objektivna odgovornost; prispevek oškodovanca; pristojnost Ustavnega sodišča; ustavno civilno pravo